MANAGEMENT INNOVATION AND FINANCIAL PERFORMANCE: THE CASE OF AMOEBA MODEL IN CHINESE ENTERPRISES - Yilana; Batbayar, Altan-Erdene; Enkh-Amgalan, Tsetsegdelger (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study investigates the financial impact of Amoeba management, a decentralized organizational model emphasizing internal accountability and profitbased autonomy, on firms operating in diverse industries across China. Using panel data from 2010 to 2023 and applying a Difference-in-Differences (DID) framework, we compare changes in both Return on Assets and Return on Equity between firms that adopted the Amoeba model and comparable non-adopting firms. The analysis reveals that seven out of eight industry pairs exhibited positive treatment effects, with particularly strong improvements observed in production-intensive sectors such as dairy, steel, beverage, and heavy machinery manufacturing. To ensure robustness, we also compute DID estimates using three-year averages before and after adoption, which confirm the main findings. Results vary across industries, with one sector (e-commerce) showing a negative effect and several others indicating that Amoeba adoption may help mitigate losses during challenging periods.